2015
DOI: 10.1155/2015/839684
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Receptor Expression on Normal Blood CD56+NK-Cells Elucidates Cell Partners That Comigrate during the Innate and Adaptive Immune Responses and Identifies a Transitional NK-Cell Population

Abstract: Studies of chemokine receptors (CKR) in natural killer- (NK-) cells have already been published, but only a few gave detailed information on its differential expression on blood NK-cell subsets. We report on the expression of the inflammatory and homeostatic CKR on normal blood CD56+low CD16+ and CD56+high  CD16−/+low NK-cells. Conventional CD56+low and CD56+high NK-cells present in the normal PB do express CKR for inflammatory cytokines, although with different patterns CD56+low NK-cells are mainly CXCR1/CXCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 98 publications
0
38
0
1
Order By: Relevance
“…CXCR1 and CXCR2 are highly expressed by cytotoxic CD56 dim NK cells ( 37 , 38 ). We recently showed that CXCR2 expression is downregulated on tumor-infiltrating NK cells in RCC and genetic modification to re-express CXCR2 enhanced recruitment of NK cells to the tumor site ( 39 ).…”
Section: The Role Of Cxcr1 and Cxcr2 In Solid Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…CXCR1 and CXCR2 are highly expressed by cytotoxic CD56 dim NK cells ( 37 , 38 ). We recently showed that CXCR2 expression is downregulated on tumor-infiltrating NK cells in RCC and genetic modification to re-express CXCR2 enhanced recruitment of NK cells to the tumor site ( 39 ).…”
Section: The Role Of Cxcr1 and Cxcr2 In Solid Malignanciesmentioning
confidence: 99%
“…CXCR3 is expressed on different subtypes of T and NK cells ( 37 , 44 ) and binds to CXCL9, CXCL10, and CXCL11. During homeostasis, CXCL9, CXCL10 and CXCL11 are expressed at low levels by monocytes, endothelial cells and fibroblasts, but are upregulated upon cytokine stimulation, especially by IFNγ and TNFα ( 45 , 46 ).…”
Section: The Role Of Cxcr3 and Its Ligands In Solid Tumorsmentioning
confidence: 99%
“…This receptor is expressed on several immune cells, including activated T cells [40][41][42][43], dendritic cells [79,80] and NK cells [81], but not on resting T cells, B cells, monocytes, or granulocytes [34]. Non-immune cells such as fibroblasts, endothelial, epithelial and smooth-muscle cells also express this receptor [38,82].…”
Section: Cxcr3 Functions and Its Ligandsmentioning
confidence: 99%
“…13 For instance, the IL-8 chemokine receptors CXCR1 and CXCR2 are expressed on CD56 dim CD16 + NK cells and mediate recruitment into tissues. 14,15 NK cells are known for exerting direct perforin/ granzyme B-mediated cytotoxicity against tumor cells in the tissue. Alternatively, it was recently reported that NK cell cytokine secretion can arrest tumor cell growth through sensing of PDGF-DD via Nkp44 on NK cells.…”
Section: Introductionmentioning
confidence: 99%